Promoting physical activity during the COVID-19 lockdown in Australia: The roles of psychological predictors and commercial physical activity apps. (September 2021) - Petersen, Jasmine M.; Kemps, Eva; Lewis, Lucy K.; Prichard, Ivanka
Abstract: Purpose: Physical activity confers many physical and mental health benefits. Thus, it is of great concern that the COVID-19 lockdown has adversely impacted engagement in physical activity. There is a need to understand the factors linked to physical activity during COVID-19 as this will be fundamental to the development of innovative approaches to support engagement in physical activity during a pandemic. This study aimed to ascertain the psychological and mental health predictors of physical activity during the COVID-19 lockdown. We also examined the value of harnessing commercial physical activity apps to facilitate physical activity during a pandemic. Method: A nationwide online survey was completed by 408 Australian adults (Mage = 35.7 ± 13.9 years, 86.0% female) following the initial COVID-19 lockdown (April/May 2020). The survey incorporated measures that retrospectively assessed physical activity (and perceived changes in physical activity behaviour), psychological constructs (social support, self-efficacy, self-determined motivations), mental health, and engagement with commercial physical activity apps during the lockdown. Results: Over half of participants (53.4%) reported a reduction in physical activity during the initial COVID-19 lockdown, with markedly fewer (23.8%) reporting an increase in physical activity. App use (β = .09, p  = .027), social support (β = .10, p  = .021), self-efficacy (β = .42, p  < .001), and identified regulation (β = .25, p  < .001) emerged as important predictors of physical activity engagement (min/week). Self-efficacy (OR = 4.2, p  < .001) was also associated with a greater likelihood of perceived positive changes (increases) in physical activity. The relationship between app use and physical activity was mediated by self-efficacy ( β  = 0.10 [0.06, 0.15]) and identified regulation ( β  = 0.09 [0.04, 0.15]); self-efficacy (β = 0.15, [0.09, 0.21]) also mediated the relationship between app use and positive changes in physical activity. Conclusions: It is imperative that interventions targeted at increasing social support, self-efficacy, and autonomous motivations are developed and utilised to support engagement in physical activity during a pandemic. Commercial physical activity apps demonstrate the potential to mitigate reductions in physical activity during a pandemic, and thus the use of these apps should be encouraged. Highlights: Over half of participants reported a reduction in physical activity during the initial COVID-19 lockdown in Australia. App use, social support, self-efficacy and identified regulation predicted physical activity during the lockdown. Self-efficacy was associated with a greater likelihood of perceived positive changes (increases) in physical activity. The relationship between app use and physical activity was mediated by self-efficacy and identified regulation. Self-efficacy also mediated the relationship between app use and positive changes in physical activity.